2019
DOI: 10.3386/w26530
|View full text |Cite
|
Sign up to set email alerts
|

The Old Boys' Club: Schmoozing and the Gender Gap

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…In a different study, about a different topic, we have data from this same firm spanning four years. We show that the annual promotion rate is 16.5%, and that over a period of four years, over half of employees are promoted at least once (Cullen and Perez-Truglia, 2019).…”
Section: Descriptive Statistics and Randomization Balancementioning
confidence: 85%
See 1 more Smart Citation
“…In a different study, about a different topic, we have data from this same firm spanning four years. We show that the annual promotion rate is 16.5%, and that over a period of four years, over half of employees are promoted at least once (Cullen and Perez-Truglia, 2019).…”
Section: Descriptive Statistics and Randomization Balancementioning
confidence: 85%
“…Employees may feel demoralized about horizontal comparisons because, given their common responsibilities, they perceive these salary differences as unfair Breza et al (2018). Employees may think that these horizontal salary differences are due to unmeritocratic factors such as luck or workplace connections (Cullen and Perez-Truglia, 2019). 23 Employees may find it easier to justify vertical inequality because, for instance, they may think that managers deserve higher salaries because they add more value to the firm or because they worked hard to get to that position.…”
Section: Mechanisms: Social Preferencesmentioning
confidence: 99%
“…The phenomenon known as "the old boys' club" refers to the advantage that males have over their female colleagues in interacting with powerful male leaders. For example, when male employees are assigned to male managers, they are promoted faster than their female counterparts [12]. Lack of women at higher ranks and social norms related to traditional gender role expectations may reinforce and perpetuate this cycle.…”
Section: Gender Inequality In Academia Is Not Newmentioning
confidence: 99%
“…Our paper contributes to the literature on the importance of social networks. Prior research has found that networks formed through gender or race homophily have important impacts on career outcomes (Cullen and Perez-Truglia, 2019;Sarsons, 2019;Zeltzer, 2020).…”
Section: Introductionmentioning
confidence: 99%